MENINGKATKAN LITERASI AL-QUR’AN GENERASI MUDA MELALUI PEMBELAJARAN TAJWID - Ifa Dini Aminati; Saryadi; Muhammad Abu Nadlir (khidmatan, 2025)
This community service activity was conducted at Al-Ikhlas Mosque, Kempul Hamlet, Menoreh Village, Salaman District, Magelang Regency, primarily targeting local children and youth. The main problem identified was the inadequate application and understanding of Tajwid rules during Qur'an recitation, where learners generally focused only on hijaiyah pronunciation without grasping the correct principles. The goal of this program was to increase the interest in reading the Qur'an and ensure the participants' recitation adheres to Tajwid rules. The method employed was Participatory Action Research (PAR), which allowed the youth generation to actively participate in the learning process. The action program, consisting of direct face-to-face teaching, was implemented over 30 days, commencing from February 24, 2025, to March 25, 2025, supported by the development of a simple Tajwid module and guidebook. The result of this service demonstrated a significant improvement in the children's ability to recite the Qur'an in accordance with Tajwid rules, simultaneously enhancing their sense of ownership and motivation in Qur'an literacy practice.